Mutations in NOTCH3 Gene may Promote the Clinical Presentation of Spinocerebellar Ataxia Type 37 Caused by Mutations in DAB1 Gene - Wang, Zhao-Wei; Wang, Li-Ping; Du, Ye; Liu, Qi (Frontiers in Molecular Biosciences, 2021)
Background: Autosomal dominant spinocerebellar ataxia type 37 (SCA37) and Cerebral autosomal dominant arteriopathy with subcortical infarct and leukoencephalopathy (CADASIL) result from DAB1 and NOTCH3 gene mutations, respectively. Methods: In addition to conventional diagnostic methods, next-generation sequencing (NGS) and Sanger sequencing were performed to define and confirm the DAB1 and NOTCH3 gene mutation for a Chinese pedigree. Bioinformatics analysis was also applied for the mutated DAB1 and NOTCH3 protein using available software tools. Results: Brain magnetic resonance imaging shows diffuse leukoencephalopathy and cerebellar atrophy in the proband. NGS and Sanger sequencing identified two novel heterozygous mutations: NM_021080:c.318T > G (p.H106Q) in the DAB1 gene and NM_000435:c.3298C > T (p.R1100C) in the NOTCH3 gene. Bioinformatics analysis suggested that the DAB1 and NOTCH3 gene mutations are disease-causing and may be responsible for the phenotypes. Conclusion: This is the first report of a pedigree with both SAC37 and CADASIL phenotypes carrying corresponding gene mutations. Mutations in the NOTCH3 gene may promote the clinical presentation of spinocerebellar ataxia type 37 caused by mutations in the DAB1 gene. In addition to general examinations, it is vital for physicians to apply molecular genetics to get an accurate diagnosis in the clinic, especially for rare diseases.